Leveraging social media for resilient cultural heritage: a people-centred conceptual framework for community engagement and crisis response - Manal Ginzarly; Jacques Teller (Built Heritage)
Abstract In the face of climate change, cultural heritage (CH) is vulnerable to risks, yet it is a powerful source of resilience. As efforts in climate change adaptation and disaster risk reduction progress, CH plays a crucial role in strengthening communities’ capacity to recover and adapt. International frameworks such as the Hangzhou Declaration and the Sendai Framework emphasise the integration of CH into people-centred strategies for strengthening community resilience. This paper develops a people-centred conceptual framework that explores the intersection of CH, community resilience, and digital tools, drawing on emerging theories in heritage and resilience studies, particularly in relation to digital practices. The framework advocates for more inclusive and locally contextualised practices by engaging communities in the co-construction of heritage values and enhancing multivocality through digital platforms. It highlights the transformative role of digitally mediated heritage practices, from digitisation and crowdsourcing to active community participation in crisis response. Despite the growing potential of digital tools, significant challenges remain, such as data bias, unequal access, and the need for a more holistic approach that overcomes both traditional rigid differentiation and the split between tangible and intangible heritage, as well as between heritage by designation and heritage by appropriation. This study offers future directions for developing more resilient heritage practices, focusing on the equitable inclusion of diverse community voices in shaping CH preservation and resilience strategies.